Performance Improvement Through Talent Management, Career Development and Education in Mantri of PT Bank Rakyat Indonesia (BRI) Tbk Teluk Betung Branch - Fadlika Fadlika; Yudhinanto Cahyo Nugroho; Maria Septijantini Alie; Hasbullah Hasbullah; Eka Travilta Oktaria; Desi Derina Yusda (Journal of Economics and Management Scienties, 2026)
This study investigates the influence of talent management, career development, and education on the performance of "Mantri" officers at PT Bank Rakyat Indonesia (BRI) Tbk, Teluk Betung Branch. The research addresses a significant gap in the literature concerning field level employees within microfinance banking. Using a quantitative approach with a census of 52 Mantri officers, data were collected via structured questionnaires and analyzed using multiple linear regression. The results reveal that each independent variable talent management, career development, and education has a statistically significant and positive effect on employee performance. Talent management emerged as the most dominant predictor, followed by education and career development. The simultaneous test (F-test) confirmed the model's overall significance, with an R Square value of 0.900, indicating that 90% of the variance in employee performance is explained by the three variables. These findings suggest that integrating human resource practices can substantially enhance performance outcomes, particularly in dynamic frontline roles. This study contributes empirical evidence to support the implementation of strategic HR frameworks in regional banking and underscores the necessity for performance focused talent policies tailored to microfinance service contexts.